Factors Associated With Laser Trabeculoplasty Response Duration: Analysis of a Large Clinical Database (IRIS Registry). Issue 10 (October 2021) - Chang, Ta Chen; Vanner, Elizabeth A.; Fujino, Danielle; Kelly, Scott; Parrish, Richard K.
Abstract : Précis: In eyes with trabeculoplasty response, those with lower baseline pressure, angle recession or uveitis had shorter survival. Eyes without medications before treatment remained medication-free for a median of 197 days. Purpose: We examined patients in a large clinical registry to assess factors associated with laser trabeculoplasty (LTP) response durations. Methods: This is a retrospective cohort study with LTP patients in the Intelligent Research in Sight Registry. Data were extracted if the eye had a LTP procedure code and a glaucoma diagnosis. In responders [≥20% intraocular pressure (IOP) reduction], any post-LTP IOP that was above 80% of baseline was considered a failure event. Eyes were censored if IOP-lowering medication/procedure was added/performed, or if the eye reached the end of follow-up. First eye of bilaterally treated patients were included. Results: A total of 79, 332 patients/eyes were included; 53.2% female; mean age 71.5 years; 64.5%White; 71.2% primary open angle glaucoma. Mean baseline IOP was 21.6±5.3 mm Hg (2.1±1.5 medications). Eyes with higher baseline IOP had longer survival (>24 mm Hg median 349 d; 18 to 24 mm Hg median 309 d; <18 mm Hg median 256 d, P <0.001 for all comparisons). Overall failure at 0, 6, 12, 18 and 24 months were 0.2%, 6.1%, 16.8%, 29.1%, and 40.8%. Angle recession and uveitis increased the risk of failure (hazard ratios 1.69 and 1.80, respectively). Eyes without medications at baseline remained medication-free for a median of 197 days (interquartile range 106, 395 d). Conclusions: Angle recession and uveitis increase the risk of LTP failure. LPT may be effective in prolonging medication-free IOP-control in some patients. Abstract : Supplemental Digital Content is available in the text.